Current status and prospect of diagnosis and treatment of bone metastasis of thyroid cancer - ZHAO Yihan, LI Ruochen, LIN Yansong (Zhongguo aizheng zazhi)
For differentiated thyroid cancer (DTC), which accounts for over 90% of cases and usually has a good prognosis, bone metastasis is not only the main threat to patients’ survival and quality of life, but also a difficult problem that needs to be solved urgently in clinical diagnosis and treatment at this stage. Currently, existing clinical guidelines at home and abroad have not yet provided comprehensive management recommendations and precise diagnostic and treatment strategies for bone metastasis in thyroid cancer, making it imperative to promote the implementation of systematic and personalized diagnostic and treatment plans. Therefore, understanding epidemiological characteristics, clarifying the pathogenesis, mastering commonly used diagnostic techniques, exploring the latest treatment progress and evaluating treatment efficacy are crucial for the management of bone metastasis in thyroid cancer. In terms of pathogenesis, bone metastasis in thyroid cancer is mostly osteolytic, regulating the interaction between the bone microenvironment and cancer cells through the release of various cytokines, thus forming a vicious cycle of bone metastasis. Early identification of bone metastasis in DTC is crucial for improving patient prognosis. Its diagnosis can be based on clinical manifestations (such as bone pain, pathological fractures, spinal cord compression and hypercalcemia), laboratory tests (such as red blood cell and platelet counts, serum calcium/phosphorus and bone turnover markers), and imaging examination results [such as X-ray, computed tomography (CT), magnetic resonance imaging (MRI), single photon emission computed tomography (SPECT)/CT, and positron emission tomography (PET)/CT]. The treatment of DTC bone metastasis involves multiple modalities, such as surgical treatment, interventional radiological treatment and external beam radiation therapy for local lesions, or the use of radionuclides (131I, 89Sr and 153Sm), tyrosine kinase inhibitors (lenvatinib, sorafenib, etc.), or bone-targeting agents (including zoledronic acid, denosumab and 99Tc-methylene diphosphonate) to control the development of systemic bone metastasis. After the treatment of DTC bone metastasis, an efficacy evaluation should be conducted to guide subsequent treatment decisions and predict prognosis. With the increasingly mature multidisciplinary collaborative diagnosis and treatment model today, the diagnosis and treatment of bone metastatic DTC should include surgery, nuclear medicine, radiation and interventional therapy, external beam radiation therapy, medical oncology and clinical laboratory testing to ensure a comprehensive assessment of the patient’s condition, make objective decisions on individualized treatment plans, and achieve the goal of preventing disease progression and alleviating symptoms. This article mainly reviewed the epidemiology, pathogenesis, diagnostic methods, treatment strategies and efficacy evaluation of bone metastasis, aiming to clarify the diagnostic and treatment thinking of bone metastasis in thyroid cancer, assist in clinical management, and provide useful references for clinicians to make rapid and accurate diagnosis and precise treatment decisions when facing patients with bone metastatic DTC.